2005
DOI: 10.1016/j.neuron.2005.01.041
|View full text |Cite
|
Sign up to set email alerts
|

Nigrostriatal Dopaminergic Deficits and Hypokinesia Caused by Inactivation of the Familial Parkinsonism-Linked Gene DJ-1

Abstract: The manifestations of Parkinson's disease are caused by reduced dopaminergic innervation of the striatum. Loss-of-function mutations in the DJ-1 gene cause early-onset familial parkinsonism. To investigate a possible role for DJ-1 in the dopaminergic system, we generated a mouse model bearing a germline disruption of DJ-1. Although DJ-1(-/-) mice had normal numbers of dopaminergic neurons in the substantia nigra, evoked dopamine overflow in the striatum was markedly reduced, primarily as a result of increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
357
1
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 491 publications
(386 citation statements)
references
References 26 publications
27
357
1
1
Order By: Relevance
“…Prior studies have shown that these inhibitory effects of quinpirole are abolished in mice lacking all D2 receptors, but are retained in mice expressing only the short isoform, which serves presynaptic autoreceptor functions (32,38,39). Interestingly, similar compromises of D2 autoreceptor-mediated functions have been reported in another PD mouse model, DJ-1 Ϫ/Ϫ mice, which also exhibited reduced responses in locomotor activity to quinpirole and reduced responses of nigral neurons to dopamine and quinpirole (26). These results raise the possibility that the D2 autoreceptor-mediated function may be a converging common target of PD mutations, a notion supported by the clinical efficacy of D2 receptor agonists in PD (40).…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Prior studies have shown that these inhibitory effects of quinpirole are abolished in mice lacking all D2 receptors, but are retained in mice expressing only the short isoform, which serves presynaptic autoreceptor functions (32,38,39). Interestingly, similar compromises of D2 autoreceptor-mediated functions have been reported in another PD mouse model, DJ-1 Ϫ/Ϫ mice, which also exhibited reduced responses in locomotor activity to quinpirole and reduced responses of nigral neurons to dopamine and quinpirole (26). These results raise the possibility that the D2 autoreceptor-mediated function may be a converging common target of PD mutations, a notion supported by the clinical efficacy of D2 receptor agonists in PD (40).…”
Section: Discussionmentioning
confidence: 65%
“…Immunohistochemical analysis and stereological DA neuron counting, as well as intracellular recordings of nigral neurons, were performed as previously described (26). For immunohistochemical analysis, coronal brain sections were stained with antibodies to TH (Chemicon), total ␣-synuclein (4D6; Abcam) or phosphorylated at Ser-129 (Wako), ubiquitin (Abcam), total tau or phosphorylated tau at Ser-396/404 (PHF-1) or at Ser-202 (CP13) (both were provided by Peter Davies), and glial fibrillary acidic protein (GFAP; Sigma).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that DJ-1 has multiple functions including anti-oxidant and chaperone functions associated with PD pathogenesis (Menzies et al, 2005;Xu et al, 2005;Zhou et al, 2006). However, DJ-1 deficiency or loss-of-function leads to oxidative stressinduced cell death in vitro and in vivo (Chen et al, 2005;Goldberg et al, 2005;Kim et al, 2005). Although anti-oxidant enzymes have been considered as potential therapeutic agents against oxidative stress-mediated diseases, the enzymes inability to enter cells hinders this despite its apparent potential.…”
Section: Discussionmentioning
confidence: 99%
“…14 DJ-1 knock-out (KO) mice and flies showed increased vulnerabilities to neurotoxic agents but no signs of dopaminergic cell death. [15][16][17] PD families may also present missense mutations of DJ-1 in homozygous (L166P, M26I and E64D) and heterozygous forms (A104T and D149A). 14 How these mutants abolish or modify DJ-1 functions is a matter of debate, as a common mechanism of action for the various DJ-1 mutants is still lacking.…”
mentioning
confidence: 99%